Gender-Based Employment Segregation : Understanding Causes and Policy Interventions - Das, Smita (World Bank, Washington, DC, 2019)
Employment segregation—the unequal distribution of female and male workers across and within jobtypes—is often at the heart of gender gaps in job quality, wage and employment trajectories. Employment segregation carries important costs for the economy, particularly in countries facing a demographic crunch, a dearth of talent among job applicants, or an increasing proportion of households in which women are the primary bread earners. Nevertheless, employment segregation appears to be resilient to economic development and market forces, and it remains present in developed and developing countries alike. This paper discusses the factors that drive employment segregation, and policy prescriptions suggested by the literature. While prescriptions are highly dependent on local context, government policies are most likely to be effective if they strategically address the supply-side and demand-side constraints that are binding for a particular context, address several constraints in parallel if they are simultaneously binding, and carefully consider general equilibrium effects.